Prevalence of hemoglobin abnormalities in apparently healthy population in Benin. - ZOHOUN, ALBAN GILDAS COMLAN; BAGLO, TATIANA; ZOHOUN GUIDIBI, LUTECIA MYRIAM; ANANI, LUDOVIC YAOVI (My University, 2020)
Background: Sickle cell disease is the most common monogenic disorder in humans and is a major public health concern in sub-Saharan Africa. In Benin, the prevalence of sickle cell disease is estimated to be 4.8%. Our study aimed to describe the prevalence of hemoglobin abnormalities in an apparently healthy Benin population. Methods: One thousand four hundred and eighty-three men and women, apparently in good health after medical screening, were tested for hemoglobin abnormalities by hemoglobin electrophoresis and the Emmel test. Subjects who were found to have homozygous or double heterozygous hemoglobin abnormalities, were re-sampled and a confirmation hemogram and hemoglobin electrophoresis test by capillary electrophoresis was performed. Results: Our study population was predominantly male (97.7%) with an average age of 21.3 years. 1390 subjects reported that they did not know their hemoglobin electrophoresis status. Hemoglobin electrophoresis profiles found were as follows: 1077 (72.6%) AA (normal), 238 (16.1%) AS, 161 (10.9%) AC, 3 (0.2%) SC, 4 (0.2%) CC and 0 (0%) SS. The 406 subjects with abnormal hemoglobin had balanced somatic growth, with general physical examination results showing no abnormalities. In the seven subjects with major sickle cell syndrome or hemoglobinosis (SC and CC), their values of various hemogram parameters were normal apart from the discreet presence of microcytic anemia. Conclusion: Our study highlights the need for increased routine testing of hemoglobin abnormalities and newborn screening for sickle cell disease in order to enhance early disease detection, prevention and comprehensive care.
Keywords: Sickle cell disease; Hemoglobin electrophoresis; Newborn screening; Benin